4CPS-084 Evolution of nonoccupational postexposure prophylaxis use since 2010 in a third-level hospital. (March 2019) - Garcia, L; Bécares, FJ; Arias, MÁ; de Gorostiza, C; Cordero, A; Ardizone, B; Tortajada, E
Abstract : Background: Nonoccupational postexposure prophylaxis (PEP) is a strategy to prevent new potential cases of human immunodeficiency virus (HIV) when primary prevention fails. However, it should never replace safe-sex practices. Purpose: We aimed to analyse the evolution in PEP use in our hospital in the past 8 years. Also, we wanted to evaluate its long-term efficacy in avoiding new HIV cases. Material and methods: We obtained data from our PEP dispensation register from 2010 to 2018, completing that with information concerning clinical history. We checked if people on this register had antiretroviral dispensations for HIV treatment over these 8 years in order to detect new HIV cases among users of PEP. Results: We studied 1240 cases between 2010 and 2018 (92.6% men, 7.4% women). The use of PEP grew in our hospital from 43 cases in 2010 to 317 cases in 2018. Median age was consistent through the years and it was about 32–33 years' old. The main age group was that between 25 and 45 years' old (75.02%; constant through all the years (67.86%–82.03%)). However, the age range widened through the years, including people between 19 and 75 years in 2018. Ninety-nine persons had received PEP in our hospital more than once in the past 8 years (between two and six times, being twice the more frequent case). Among PEP users, 2.18% contracted HIV at some time during the study period. Most of them got the infection much after their PEP dispensations. Five of them had been diagnosed in the basal analysis at the beginning of their PEP treatment, so they might have been previously infected. Only two cases were detected during the 6 months after PEP, so this could be a PEP failure. All of them had had unsafe sex. Conclusion: Despite PEP having shown efficacy in HIV prevention, people who misuse it and disparage safe sex, have the risk of long-term HIV infection in future episodes and, moreover, risk other sexual transmission infections. Knowing the profile of PEP user and misuser (in our case young men about 33 years' old) can help pharmacists develop educational strategies focused on encouraging primary prevention. Reference and/or acknowledgements: WHO. Risks of Unsafe Sex and AIDS . http://www.who.int/whr/media_centre/factsheet1/en/ No conflict of interest.